Influence of the concentration of chenodeoxycholic acid on the performance of the N719 dye - Najm, A. S.; Ahmad Ludin, Norasikin; Jaber, Israa; Hamid, Norul Hisham; Naeem, Hasanain Salah (Elsevier, 2022)
The influence of the Chenodeoxycholic acid (CDCA) at different concentrations on the spectroscopic and photovoltaic performances of the N719 dye was determined. Absorption analyses revealed the excellent capacity of the CDCA in stabilizing the N719 dye. The N719 dye exhibited hydroxyl and carboxylic functional groups that were accountable for the strong interactions and fast transport of electrons to the TiO2 surface. The photoluminescence emission spectroscopy of the CDCA-incorporated dye exhibited the feasibility of a large photocurrent generation. The interaction mechanism of CDCA within the N719 dye influenced the efficiency of the fabricated cell because the high photoconversion efficiency of 4.07% was recorded for 0 mM CDCA. This finding was because CDCA decreased the electrolyte contact with the N719 dye, resulting in charge accumulation in the electrolyte and decreased electron density in the N719 dye. Present findings are beneficial for the development of efficient dye-based DSSCs.